Теория и методы автоматизации проектирования вычислительных систем: перевод с английского - Прейсс Р. Дж. Ральф Дж.; Шефф Б. Г. Бенсон Г.; Янг С. Р.; Райков Л. Д. Леонид Дмитриевич (Москва, Мир, 1977)
Доп. тит. лист